Angina pectoris with normal coronary arteries in Shy-Drager syndrome. Issue 10 (October 1979) - Silverberg, R; Naparstek, Y; Lewis, B S; Levy, M
Abstract : A patient with Shy-Drager syndrome who presented with severe angina pectoris is described. Special investigations of his autonomic nervous system showed sympathetic and parasympathetic dysfunction with supersensitive end-organ response. Sympathetic dysfunction manifested as labile hypertension, severe postural hypotension, and inadequate heart rate response to atropine and the Valsalva manoeuvre. These changes in blood pressure were accompanied by severe disabling angina pectoris. Selective coronary angiography showed normal coronary arteries. It is suggested that angina pectoris resulted from the inadequate circulatory response and is another clinical manifestation of the Shy-Drager syndrome.